2005
DOI: 10.1650/7807
|View full text |Cite
|
Sign up to set email alerts
|

Geography of Spring Landbird Migration Through Riparian Habitats in Southwestern North America

Abstract: Migration stopover resources, particularly riparian habitats, are critically important to landbirds migrating across the arid southwestern region of North America. To explore the effects of species biogeography and habitat affinity on spring migration patterns, we synthesized existing bird abundance and capture data collected in riparian habitats of the borderlands region of the U.S. and Mexico. We determined the importance of geographic factors (longitude and latitude) in explaining variation in abundances an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 12 publications
1
39
0
Order By: Relevance
“…Although use of stopover sites in the Caribbean and Latin America is relatively unknown (but see Latta andBrown 1999, Deppe andRotenberry 2008), in eastern North America deciduous forest is widely available, and it is hard to believe that stop-over habitat is typically limiting in this region. In the American West, where much of the habitat is arid grasslands or alpine habitats, riparian vegetation is likely critical to the movements of many migrants and is potentially limiting; recent studies have identified adaptations associated with movements in this relatively harsh environment (Griffis-Kyle and Beier 2005, Skagen et al 2005, van Riper III et al 2008. Many species in this region make molt-migrations in midsummer, when they leave their breeding area and fly to parts of Arizona, New Mexico, and Mexico affected by monsoonal rains.…”
Section: Research Priorities During Migrationmentioning
confidence: 99%
“…Although use of stopover sites in the Caribbean and Latin America is relatively unknown (but see Latta andBrown 1999, Deppe andRotenberry 2008), in eastern North America deciduous forest is widely available, and it is hard to believe that stop-over habitat is typically limiting in this region. In the American West, where much of the habitat is arid grasslands or alpine habitats, riparian vegetation is likely critical to the movements of many migrants and is potentially limiting; recent studies have identified adaptations associated with movements in this relatively harsh environment (Griffis-Kyle and Beier 2005, Skagen et al 2005, van Riper III et al 2008. Many species in this region make molt-migrations in midsummer, when they leave their breeding area and fly to parts of Arizona, New Mexico, and Mexico affected by monsoonal rains.…”
Section: Research Priorities During Migrationmentioning
confidence: 99%
“…L.) and Russian olive (Elaeagnus angustifolia L.) (Table 1) Scott et al, 2009). Riparian ecosystems support a large proportion of SAWNA invertebrate, amphibian, reptile, mammal, and breeding bird species (Warner & Hendrix, 1984;Knopf & Samson, 1994;Naiman et al, 2005), are critical habitat for Neotropical migrant birds (Skagen et al, 2005), and supply the allochthonous stream inputs that support aquatic communities (Naiman et al, 2005).…”
Section: Study Areamentioning
confidence: 99%
“…As ecotones located at the intersection of land and water, riparian zones are exceptionally rich in biodiversity (Naiman and Décamps, 1990;Naiman et al, 1993). They represent ecological corridors (Rodriguez-Iturbe et al, 2009) and provide a crucial habitat for terrestrial animals and for migrating birds (Hilty and Merenlender, 2004;Machtans et al, 1996;Skagen et al, 1998Skagen et al, , 2005. The width of a zone can range from a few metres to several kilometres.…”
Section: Introductionmentioning
confidence: 99%